Combining Lean Service and DMAIC Stage to Reduce the Lead Time for the Procurement of Critical Care Products - Chin, Jacky; Manurung, Hasiholan; Kusumah, Lien Herliani; ‎ , Herlina (KnE Social Sciences, 2024)
Currently, the development of the health care industry is very rapid. The rapid development of health services will have an impact on increasing the elements of their supporting activities. One of the supporting activities is the procurement of medical equipment. Procurement cases often do not go well, so procurement is not on time. This is due to the very long lead time. This has an impact on decreasing customer satisfaction. Companies try to overcome this problem to be able to compete in the market. This study aims to help companies eliminate waste that occurs in the procurement process so that customer satisfaction is obtained. The approach used is Lean Service with VSM as a process flow mapping tool. Focus Group Discussion was used in the analysis of problems and solutions for improvement. Based on the FGD, there are three problems, namely, the delivery of goods, project creation, and billing documents. The results showed that the overall lead time of the critical care procurement process decreased from 216 days to 110 days, or by 45%. Keywords: critical care, lead time, lean service, procurement, value stream mapping